The Historian in the Maelstrom of History and the Long Twentieth Century in Loewenstein’s Faith in Progress - Hermann, Tomáš (Dějiny – teorie – kritika, 2009)
The article is concerned with the discussion of the nineteenth century in Bedřich Loewenstein’s Víra v pokrok (Faith in Progress) in the context of Loewenstein’s life and work. In the first part the author of the article considers in detail the genesis of Loewenstein’s work from his youth to the present day, and places it in the context of twentieth-century Czech historiography. Both from the point of view of Loewenstein’s long-term research interests and in his latest magnum opus as their syntheses the author describes the longest passage about the ‘long century’ as the actual core and intellectual focus of the book. Another perspective, of equal status, is disbelief in progress, that is, scepticism and disillusion, here forming an inner tension in the book. In a detailed report on the content and structure of Loewenstein’s account of the nineteenth century, mutually conditioned processes of the fundamental historicization and biologization of European thought emerge as being of key importance.